Autopsy of Hair Dye Poisoning –Revisited (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
With hair dyes gaining in popularity as an easy method of poisoning, either by suicide or homicide, its incidence has been rising in many regions of the country. Due to the various toxins present, the poisoning presents itself in a variety of ways. Some findings go unnoticed during hospitalisation and are apparent only after the death of the patient, during autopsy. Hence, autopsy of the cases will help to reveal these findings and will help us to better manage the patients in future, by keeping an eye out for these manifestations. Here, we present a case report along with a review of literature on the same topic.
Keywords: Hair dye; Poisoning, PPD; Oedema,; Rhabdomyolysis; Death; Autopsy